When you multiply 2 "square root expressions", you can put the multiplication problem under 1 square root. So,
√(6x) * √(3x2) = √(6x)*(3x2)
Follow the normal rules to multiply the expression under the square root,
√(18x3)
Now put this expression in simple radical form, if required, which means factoring out all the "perfect squares" from under the square root.
Factor 18 into 9*2 because 9 is a perfect square (3*3)
Factor x3 into x2 * x because x2 is a perfect square
√18x3 = √(9x2 * 2x) = √9x2 * √2x
√9x2 = 3x (because 3*3=9, x*x = x2, so 3x * 3x = 9x2)
√9x2 * √2x = 3x * √2x, which can also be written 3x√2x